SARS-CoV-2 Nsp14 protein associates with IMPDH2 and activates NF-κB signaling - Li, Tai-Wei; Kenney, Adam D.; Park, Jun-Gyu; Fiches, Guillaume N.; Liu, Helu; Zhou, Dawei; Biswas, Ayan; Zhao, Weiqiang; Que, Jianwen; Santoso, Netty; Martinez-Sobrido, Luis; Yount, Jacob S.; et al. (Frontiers in Immunology, 2022)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection leads to NF-κB activation and induction of pro-inflammatory cytokines, though the underlying mechanism for this activation is not fully understood. Our results reveal that the SARS-CoV-2 Nsp14 protein contributes to the viral activation of NF-κB signaling. Nsp14 caused the nuclear translocation of NF-κB p65. Nsp14 induced the upregulation of IL-6 and IL-8, which also occurred in SARS-CoV-2 infected cells. IL-8 upregulation was further confirmed in lung tissue samples from COVID-19 patients. A previous proteomic screen identified the putative interaction of Nsp14 with host Inosine-5'-monophosphate dehydrogenase 2 (IMPDH2), which is known to regulate NF-κB signaling. We confirmed the Nsp14-IMPDH2 protein interaction and identified that IMPDH2 knockdown or chemical inhibition using ribavirin (RIB) and mycophenolic acid (MPA) abolishes Nsp14- mediated NF-κB activation and cytokine induction. Furthermore, IMDPH2 inhibitors (RIB, MPA) or NF-κB inhibitors (bortezomib, BAY 11-7082) restricted SARS-CoV-2 infection, indicating that IMDPH2-mediated activation of NF-κB signaling is beneficial to viral replication. Overall, our results identify a novel role of SARS-CoV-2 Nsp14 in inducing NF-κB activation through IMPDH2 to promote viral infection.